A ONE MAN ONLY JOB - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Fentahun Mengistu, Bahir Dar, Ethiopia: 'While I was reading the article Diet for drain dodgers in Spore No 63, my attentionwas drawn to the photo picture depicted where drain oxen are seen pulled by a farmer in the front and the other man...